A study on the microbiological status of mineral drinking water - Aditi, Faria Y.; Rahman, Shafkat Shamim; Hossain, Md Manjur (© 2017 Bentham Science Publishers B.V., 2018)
This article was published in the Open Microbiology Journal [ © 2017 Shakya et al. ] and the definite version is available at :http://doi.org/10.2174/1874285801711010031. The Journal's website is at: https://benthamopen.com/ABSTRACT/TOMICROJ-11-31